Inhibitory effects of free ammonia on Anammox bacteria - MERTOĞLU, BÜLENT; KALKAN AKTAN, ÇİĞDEM; BAKIRCI, KOZET (SPRINGER, 2012)
Anammox bacteria can effectively treat high ammonia and nitrite concentrations under anoxic environments. However, the presence of high ammonia and nitrite concentrations may cause free ammonia and nitrous acid inhibition at high pH and temperature environments. In this study, the inhibitory effect of free ammonia on Anammox bacteria was investigated in a lab-scale upflow fixed-bed reactor with Kaldnes biofilm carriers. Results of continuous operation showed that inhibition was not observed in the Anammox reactor when the free ammonia concentration gradually increased up to 150 mg/L. However, Anammox activity suddenly dropped to 10 % when the free ammonia concentration reached to 190 mg/L. Nevertheless, high influent ammonia and nitrite concentrations up to 1,500 and 500 mg/L, respectively, did not noticeably inhibit the Anammox activity. Gradually decreasing Anammox activity was also supported by fluorescent in situ hybridization (FISH) analysis. FISH and 16S rRNA gene analysis results revealed that main Anammox organisms were phylogenetically related to Candidatus Kuenenia stuttgartiensis, Candidatus Jettenia asiatica and Candidatus Brocadia anammoxidans.
Keywords: Free ammonia; Inhibition; Kaldnes rings; Anammox; Molecular tools; IN-SITU DETECTION; NITROGEN REMOVAL; START-UP; ANAEROBIC-DIGESTION; OXIDATION; NITRIFICATION; NITRITE; REACTOR; WATER; COMMUNITY